2006
DOI: 10.1007/11866763_44
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless Reconstruction of Freehand 3D Ultrasound Data

Abstract: Abstract. Freehand 3D ultrasound can be acquired without a position sensor by finding the separations of pairs of frames using information in the images themselves. Previous work has not considered how to reconstruct entirely freehand data, which can exhibit irregularly spaced frames, non-monotonic out-of-plane probe motion and significant inplane motion. This paper presents reconstruction methods that overcome these limitations and are able to robustly reconstruct freehand data. The methods are assessed on fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In recent work, we have shown that it is possible to almost completely correct the tilt bias in a sensorless reconstruction by warping it to match orientations measured by a sensor [23]. Given that we require an orientation sensor to correct the decorrelation curves, there is no reason not to correct the tilt com- Given the elevational direction of the sensor data, it is obvious that the right of the two images is the correct one, but this would not be apparent in practice where we have only orientation measurements.…”
Section: Experiments and Resultsmentioning
confidence: 98%
“…In recent work, we have shown that it is possible to almost completely correct the tilt bias in a sensorless reconstruction by warping it to match orientations measured by a sensor [23]. Given that we require an orientation sensor to correct the decorrelation curves, there is no reason not to correct the tilt com- Given the elevational direction of the sensor data, it is obvious that the right of the two images is the correct one, but this would not be apparent in practice where we have only orientation measurements.…”
Section: Experiments and Resultsmentioning
confidence: 98%
“…The untracked freehand system or sensorless method requires the operator to move the transducer in a steady and regular motion at a constant linear or angular velocity, while 2D ultrasound frames are captured to generate a 3D ultrasound image [14]. Recently, a sensorless reconstruction method has been designed using a regression-based distance measurement, interpolation techniques, and unconstrained freehand data without any limitation on the trajectory [15]. In recent study, the image-based algorithm makes use of the adaptive speckle decorrelation to learn relative position and orientation between the acquired 2D ultrasound image pairs [16].…”
Section: Sensorlessmentioning
confidence: 99%
“…These mathematical approaches made possible the following research on sensorless 3-D US reconstruction. The direction of the probe trajectory must be limited in many sensorless studies, which is a restriction, but recently, a sensorless reconstruction method has been designed using a regression-based distance measurement, interpolation techniques and unconstrained freehand data without any limitation on the trajectory (Housden et al 2006b;. A strategy for interpolation between the correlation peaks of the measured samples has enabled the tracking of simultaneous lateral and elevational motion of a transducer to be more accurate than in other similar methods (Housden et al 2006a).…”
Section: Scanning B-slices and Localizationmentioning
confidence: 99%